Efektivitas Kebijakan Pemerintah dalam Pengangkatan Tenaga Honorer Menjadi ASN melalui P3K: Tinjauan Dampak dan Implementasi - Adinda Putri Br Sitepu; Arini Maulida Sitepu; Elisman Pangondyan Siregar; Elrisa Br Barus; Santi Theresia Sinurat; Sri Rejeky Sitohang; Jamaludin Jamaludin (Lembaga Pengembangan Kinerja Dosen, 2025)
Teachers are one of the important elements in education in organizing educational achievements as mandated by the Constitution. Education as a conscious and planned effort to realize the learning process in order to develop potentials certainly requires teachers as facilitators and even the main component of the education process itself. The existence of teachers is also inseparable from the government's policy space. Qualitative research methods with descriptive analysis techniques aim to describe and summarize the phenomena studied through data collection from various sources, such as interviews, observations, and literature reviews. The policy of appointing honorary teachers to become ASN through the P3K scheme is basically a positive step that provides hope and recognition for educators who have served for a long time.